2011
DOI: 10.1007/s12013-011-9258-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Huperzine A Improves Cognition in Vascular Dementia Patients

Abstract: Huperzine A can significantly improve the cognitive function in patients with mild to moderate vascular dementia. Further, the medicament is safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…All selected trials were randomized. One trial [43] was single-blind, and the other [4] was double-blind. The description of the trial characteristics and demographics of the participants in the studies were also showed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All selected trials were randomized. One trial [43] was single-blind, and the other [4] was double-blind. The description of the trial characteristics and demographics of the participants in the studies were also showed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Augmentation of cholinergic neurotransmission with the use of cholinesterase inhibitors (ChE-Is) produces a modest improvement in cognitive function for some patients [2, 3]. VD is a type of dementia caused by a variety of cerebral vascular diseases such as cerebral hemorrhage, cerebral infarction, and subarachnoid hemorrhage [4]. More interestingly, cholinergic agents, including ChE-Is, have shown considerable benefits in VD therapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Huperzine A has been used for treating AD and mild memory deficits since 1994 in the China [55, 56]. In a randomized, double-blinded placebo-controlled clinical trial with the participation of 78 patients who have mild to moderate VaD, Huperzine A treatment significantly improved the cognitive functions in these patients [57]. Furthermore, both animal and human safety evaluations have demonstrated that Huperzine A is safe [58].…”
Section: Therapeutic Implications For Vci With Traditional Chinesementioning
confidence: 99%
“…Recently an RCT of older adults (60–80 years old) with VaD showed huperzine A improved activities of daily living (ADLs) and cognitive tests (MMSE & clinical dementia rating). 51 However, in the US, a larger clinical trial showed only a modest effect of high dosage huperzine A (400 μg twice daily) on cognition. 52 Huperzine A was well tolerated with the most common side effect being nausea.…”
Section: Huperzine Amentioning
confidence: 99%